Tabagismo e transtornos cognitivos e mentais : avaliação dessa relação em idosos do município de Porto Alegre-RS/Brasil - Ribeiro Júnior, Francisco José Pascoal (2016)
The aim of this study was to determine the association between smoking and cognitive and mental disorders in the elderly and their association with sociodemographic characteristics in a sample of patients in the city of Porto Alegre, Rio Grande do Sul, Brazil. This was a descriptive, cross-sectional and prospective data collection study, utilizing the Mini International Neuropsychiatric interview, Global Assessment Questionnaire Aging and Neuropsychological Assessment CERAD (Consotum to Establish a Registry for Alzheimer's Disease) in 580 elderly aged 60 or more. 580 elderly, there is a higher prevalence for men (73.3%), aged between 60-69 years (24.0%), single (65.3%), widowed (61.3%) without income (28 , 9%), specific phobia (28.4%), grouped phobias (26.9%) current alcohol dependence (62.5%) and alcohol dependence in life (41.2%). There was more difficulty in quitting smoking in elderly: major depressive episode throughout life (67.0%), specific phobia (65.4%), grouped phobias (66.4%), current alcohol dependence (64, 7%) and lifelong (65.5%) and any anxiety disorder (66.7%). Seniors with current alcohol dependence and grouped phobias have 2.8 and 1.5 times the prevalence of current smoking, respectively. Older people at risk of suicide have 1.3 times higher the prevalence of smoking in the present life. And older adults with alcohol dependence in life and bipolar disorder have 1.4 and 1.6 times higher smoking prevalence in life, respectively. Elderly people with dementia have 1.4 times greater prevalence to have stopped smoking compared to older people without dementia. These results indicate the presence of mental disorders in elderly smokers, calling attention to some sociodemographic characteristics and associations with some disorders that can make a difference in the diagnosis and treatment of these disorders.